A novel ultra-wideband pulse generation technique for narrowband interference mitigation - Mohammed, Ahmed R. (Kulliyyah of Engineering, International Islamic University Malaysia, 2013)
Ultra wideband (UWB) interference on narrowband systems is a serious problem, which impedes the use and development of the UWB short range wireless communication technology. The UWB pulsed signal can degrade or block signals of narrowband systems that may exist in its transmission zone. Limited solutions have so far been proposed by different researchers to mitigate the UWB interference on specific narrowband systems at the cost of UWB system performance and increased complexity. This thesis proposes a novel technique to generate UWB pulses based on an effective way of shaping a continuous sine wave rather than using one of the conventional pulses of Gaussian family. Two pulse generators for narrowband interference mitigation have been designed and implemented. A proposed technique of pulse position phase modulation (PPPM) has been validated with the proposed pulse generators as a method to double the throughput speed. It has also been demonstrated that the proposed pulse generators can support a variety of modulation and transmission techniques with different throughput speeds and interference mitigation levels.Both pulse generators comply with the Federal Communications Commission (FCC) spectrum emission indoor and outdoor masks. The first generates shaped monocycle sine wave (SM-S) pulses and the second generates shaped monocycle half wave rectified sine wave (SM-HRS) pulses. The SM-S and SM-HRS pulse generators have minimum throughputs of 550 Mbps and 500 Mbps respectively using on-off keying (OOK) modulation. The interference mitigation level with the SM-HRS pulse generator achieved -90 dBm/MHz over 0-5.5 GHz range, which is so far better than any existing mitigation level. The SM-S pulse generator on the other hand, achieved less than –70 dBm/MHz over 0-5 GHz range, which is also high by comparison with the highest values achieved by other existing solutions. Both generators avoid interference with most existing narrowband systems including GPS, PCS, WiMAX, WLAN 802.11b and 802.11a.